2013
DOI: 10.1128/aac.01826-12
|View full text |Cite
|
Sign up to set email alerts
|

Raltegravir Pharmacokinetics in Treatment-Naive Patients Is Not Influenced by Race: Results from the Raltegravir Early Therapy in African-Americans Living with HIV (REAL) Study

Abstract: Racial differences in antiretroviral treatment responses remain incompletely explained and may be a consequence of differential pharmacokinetics (PK) associated with race. Raltegravir, an inhibitor of HIV-1 integrase, is commonly used in the treatment of HIV-infected patients, many of whom are African-American. However, there are few data regarding the PK of raltegravir in African-Americans. HIV-infected men and women, self-described as African-American and naive to antiretroviral therapy were treated with ral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…In the REAL study, Wohl et al found the median concentration at 12 hours after dosing to be 0.091 µg/mL with a range of 0.010–1.386 µg/mL. 12 Despite the wide variability, 95% of subjects had an HIV RNA level below 200 copies/mL by week four of treatment. 12 In the QDMRK trial comparing once daily to twice daily dosing, the trough level with twice daily dosing was 0.128 µg/mL with a range of 0.015–1.074 µg/mL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the REAL study, Wohl et al found the median concentration at 12 hours after dosing to be 0.091 µg/mL with a range of 0.010–1.386 µg/mL. 12 Despite the wide variability, 95% of subjects had an HIV RNA level below 200 copies/mL by week four of treatment. 12 In the QDMRK trial comparing once daily to twice daily dosing, the trough level with twice daily dosing was 0.128 µg/mL with a range of 0.015–1.074 µg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…12 Despite the wide variability, 95% of subjects had an HIV RNA level below 200 copies/mL by week four of treatment. 12 In the QDMRK trial comparing once daily to twice daily dosing, the trough level with twice daily dosing was 0.128 µg/mL with a range of 0.015–1.074 µg/mL. 13 In this trial, trough levels correlated with virologic response with once daily dosing, but not with twice daily dosing.…”
Section: Discussionmentioning
confidence: 99%
“…The primary aim of the study was to determine RAL pharmacokinetics in this population compared to those derived from white patients – results that have been previously been published. 26 A secondary objective was to describe the metabolic changes of participants experienced while receiving this antiretroviral combination. In addition to being AA, inclusion criteria included having had less than seven cumulative days of prior exposure to antiretroviral therapy, a plasma HIV RNA level >1,000 copies/ml at the time of screening, an estimated glomerular filtration rate by Modification of Diet in Renal Disease (MDRD) of at least 60 ml/min/1.73 m 2 , and hepatic transaminase levels no more than three times the upper limit of normal.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the lack of an HIV-negative postmenopausal cohort makes discerning the effect of HIV infection vs menopausal status on raltegravir pharmacokinetics difficult. The differing proportion of black women among our cohorts are unlikely to confound the pharmacokinetic data presented herein, given that the Raltegravir early therapy in African-Americans living with HIV (REAL) study did not identify any raltegravir plasma pharmacokinetic differences based on race[15]. Finally, in our study premenopausal women received raltegravir in the fed state while postmenopausal women were in the fasted state.…”
Section: Discussionmentioning
confidence: 97%
“…The dynamic range for raltegravir in BP was 20-10,000ng/mL and in CVF was 50-10,000ng/mL with a minimum of 90% accuracy, and inter-and intra-day variability of 2.4-7.9% and 1.4-3.8%, respectively [15-17]. …”
Section: Methodsmentioning
confidence: 99%